Church Initiatives and Challenges in Promoting Sustainable Development in Zimbabwe - Marava, J. Moyounotsva (Current Progress in Arts and Social Studies Research Vol. 7, 2024)
The situation in the developing world has shown that the political administrative systems and structures alone cannot bring the idea of sustainable development to fruition. As such, these gaps can be filled if churches play a role through their values systems which incorporate principles of sustainable development. The church’s obligation to proclaim liberty, peace and justice for the good of the people compliments the triple concepts of globalisation, good governance and democracy which have dominated the current international discourse. However, the church has been widely recognised as just an institution championing spiritual growth and little is documented on its role in sustainable development. A study was conducted to investigate initiatives by church leaders in Zimbabwe to attain sustainable development in line with Agenda 21 which is meant to be a road map to sustainable development. A qualitative design was used in this study using questionnaires, interviews and secondary data from church archives as research instruments. This study was conducted in all 10 provinces in Zimbabwe. Data was gathered in order to establish their common faith and doctrine that distinguish them from other churches including their stance on promoting sustainable development and the challenges they face in attempting to achieve the objectives of sustainable development. A hermeneutics and philosophical analytic models were employed to analyse and interpret relevant literature. The study revealed that the church’s participation in developmental projects is tremendous. Pentecostal churches such as Zimbabwe Assemblies of God Africa (ZAOGA), Apostolic Faith Mission church (AFM), Zion Christian Church (ZCC) and mainstream churches such as the Anglican, Roman Catholic and Methodists are contributing immensely towards sustainable development. The mainline and Pentecostal churches are the leaders ahead of white garment churches in terms of supporting objectives of sustainable development. There has been the establishment of educational institutions, vocational training centres and old age people’s homes in many areas around the country. Key challenges identified that militate against the church’s efforts to contribute to sustainable development were the varying church doctrines, conservative behaviour of churches and gender imbalances as well as church politics in terms of vision to follow. Thus, the church therefore cannot afford to be indifferent and isolated in the face of glaring socio-political and economic challenges enveloping Zimbabwe. This paper has given an insight into how the progressive Zimbabwean Church leadership has been deploying all its resources in order to effectively and efficiently contribute to the attainment of sustainable development. The church has a great potential to make a meaningful contribution to sustainable development as reflected by this study. Moreso, the paper offers strong recommendations along with conclusions that could be considered by authorities/ government for necessary implementation in the future. Thus, there should be a refocus on the undermined role of the clergy in influencing sustainable development.